THE IMPACT OF THE USE OF SOCIAL MEDIA YOUTUBE ON DENOTATIVE MEANING FROM A SEMANTIC PERSPECTIVE - Kesmi Veronika Simanjuntak; Bernieke Anggita Ristia Damanik (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study explores the impact of YouTube as a social media platform on the interpretation of denotative meaning from a semantic perspective. While denotative meaning traditionally refers to the literal or dictionary definition of a word, the integration of multimodal features in YouTube—such as tone, visuals, music, and gestures—may cause shifts in how audiences perceive and interpret those meanings. Using a qualitative descriptive method, this research analyzes selected YouTube videos and their comment sections to examine how literal meanings are expressed by creators and understood by viewers. The findings show that multimodal elements often influence or even override the intended denotative meaning of words, leading to various audience interpretations. This highlights the fluidity of meaning in digital communication, where context and delivery can reshape even the most basic semantic elements. The study contributes to semantic analysis by demonstrating that denotative meaning in online platforms is no longer entirely fixed, and suggests the need for further interdisciplinary research involving semantics, pragmatics, and media discourse.